Assessment of low temperature electricity production with focus on geothermal energy - Scheyhing, Andreas (My University, 2012)
With the rise of environmental awareness and increased electricity prices, low temperature electricity production cycles are getting more and more into focus. These include applications that produce electricity from industrial waste heat, which otherwise would have been released to the environment. They can also be used for medium enthalpy geothermal heat sources from 125 to 225 °C. The purpose of this Master Thesis is to identify and compare different technologies to produce low temperature electricity, according to their profitability and efficiency. Moreover, this Thesis focuses on investigating electricity cycles for further use in geothermal power plant applications. Finally the specific case of Geotermica1 is studied. Low temperature electricity production cycles have been identified during a literature research. Based on that, the most promising cycles have been analysed in detail. These are the ORC (Organic Rankine Cycle), RORC (Regenerative Organic Rankine Cycle) and the LTD (Low Temperature Differential) Stirling engine. The analysis is carried out in Aspen + and with a modified Schmidt formula for the LTD Stirling engine according to Chen (2003). Starting with set boundaries, each cycle is researched in costume cases while varying the same heat source and sink. The LTD Stirling engine shows the best performance with 18.2% system efficiency. The simulated LTD Stirling engine, however, has a temperature limitation of 150°C and cannot be used above this temperature. For higher temperatures, up to 185°C, the highest efficiency was obtained with the RORC of 18.5%. In the Geotermica case, the LTD Stirling engine did not take part, due to missing economic data in the literature. With the expected well flows of the planned geothermal power station in the south of Italy on the Aeolian Islands and the local weather data, the RORC is most promising. The economic evaluation of the ORC and the RORC show as well, that the RORC is the most profitable, although it is the more expensive one with an investment cost of 10.2 Mio. € whereas the ORC costs 8.9 Mio. €. The RORC has an annual income of 6.3 Mio. € which is roughly 1 Mio. € more than the ORC. Together with the exploration and drilling costs of 30 Mio. €, the payback time is estimated to 6.4 years. 1 Geotermica is the company who plans to build the analysed geothermal power station in south Italy.
Keywords: Kemiteknik; Chemical Engineering